Adjuvant corticosteroid therapy in hepatosplenic candidiasis-related IRIS - Cengiz Bayram; Ali Fettah; Nese Yarali; Abdurrahman Kara; Fatih Mehmet Azik; Betül Tavil; Bahattin Tunc (Mediterranean Journal of Hematology and Infectious Diseases)
Hepatosplenic candidiasis (HSC) is a form of invasive fungal infection that occurs most commonly in patients with acute leukemia treated with chemotherapy and requires protracted antifungal therapy. Immune reconstitution inflammatory syndrome (IRIS) is best characterized as a dysregulated inflammatory responses triggered by rapid resolution of immunosuppression. We present a child diagnosed with standard-risk precursor B cell-acute lymphoblastic leukemia who developed HSC and Candida-related IRIS during recovery of neutropenia associated with induction chemotherapy. Addition of corticosteroid therapy to antifungal treatment is associated with the resolution of the clinical symptoms and laboratory findings